Incontinentia pigmenti associated to unilateral complete cleft lip in a neonatal boy. - Hui-ling, Jin; Ru-zhi, Zhang; Lei, Zhou; Cong-jun, Jiang; Wen-yuan, Zhu (European Journal of Pediatric Dermatology, 2012)
We describe an infant with characteristic cutaneous findings, which progressed through the vesicular, verrucous, and hyperpigmented stages in the first two months of life. The lesions were arranged in linear, vertical streaks that extended along the mid-posterior surface of the left lower limb from the infragluteal region to the boy’s ankle. The histological findings of the skin biopsy were compatible with the third stage of incontinentia pigmenti. The patient had no other skin lesions and did not have fever or other systemic symptoms except unilateral complete cleft lip.